Mapping the Digital Leadership Research Landscape on Industri 4.0: A Bibliometric Analysis - Prawestri, Mardika; Rahayu, Meika Kurnia Puji; Qamari, Ika Nurul (PT FORMOSA CENDEKIA GLOBAL, 2024)
Digital leadership encompasses a range of skills, actions, and practices that encourage and inspire employees during the process of digital transformation. Digital leadership focuses on innovation and corporate goals in the Industry 4.0 era. Therefore, this study aims to identify research trends on digital leadership in the Industry 4.0 era globally. This research uses a qualitative approach. All data collection and screening procedures in the Scopus database provided the foundation for this research. A total of 92 eligible published articles from 2019 to 2023 were explored and the scientific landscape was further visualised using Scopus and VOSviewer features. The study's results indicate that 2023 will see the highest volume of publications on digital leadership. The United Kingdom and the United States were recognized as the leading contributors to this body of research. The results also show evidence that the network visualisation consists of 7 clusters. The next research topics on digital leadership that provide great opportunities to be studied more deeply in the era of the industrial revolution 4.0 are e-learning, performance, artificial intelligence, digital manufacturing, digital innovation, digital capabilities, digital storage and sustainability.